P27 expression in pleomorphic salivary gland adenoma - Tarakji, Bassel; Umair, Ayesha; Altamimi, Mohammed Alsakran; Azzeghaiby, Saleh Nasser; Mahmoud, Abla Sayed; Darwish, Shourouk; Nassani, Mohammad Zakaria; Ashok, Nipun (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: This study aims to characterise alterations in the immunohistochemical expression of p27 in normal tissue of the salivary gland surrounding pleomorphic adenoma and in the tumour cells of pleomorphic adenoma. Material and methods: A retrospective study of data including 120 cases of pleomorphic adenomas (66 female, 54 male) retrieved from the files of the Oral Pathology Departments of Aleppo University, Syria and Al-Farabi Dental and Nursing College. Immunohistochemical expression against p27 was examined in the selected cases. The percentage of p27-positive nuclei was semi-quantitatively assessed by two independent observers and scores were given. The statistical analysis included the use of descriptive statistics and proportional frequencies. Results: The results showed that P27 nuclear staining with high staining (moderate to strong positive staining in more than 50% of nuclei, depending on the percentage of nuclei for the cells) was noted in tumour duct cells of pleomorphic adenoma in 90 (75%) cases out of 120, while 30 (25%) cases showed low staining (positive staining in less than 5% of nuclei, depending on the percentage of nuclei for the cells). Conclusions: Our data suggests that p27 might have a minor role in the development of pleomorphic adenoma.